Arginase I gene single-nucleotide polymorphism is associated with decreased risk of pulmonary hypertension in bronchopulmonary dysplasia - Trittmann, JK (2014)
AIM: To test the hypothesis that there are single-nucleotide polymorphisms (SNPs) in genes of the l-arginine/nitric oxide pathway associated with pulmonary hypertension (PH) in neonates with bronchopulmonary dysplasia (BPD). METHODS: Neonates with BPD were enrolled (n = 140) and clinical characteristics compared between case (BPD + PH) and control (BPD) groups. DNA was isolated from blood leucocytes and assayed for 17 SNPs in l-arginine/nitric oxide pathway genes by Sequenom massarray. Genes included carbamoyl-phosphate synthetase, ornithine transcarbamylase, argininosuccinate synthase, nitric oxide synthase and arginase. SNPs were selected from the National Center for Biotechnology Information database for their putative functionality. Calculated minor allele frequencies (MAF) of cases and controls were compared using χ(2) and logistic regression. RESULTS: Of the 140 patients with BPD, 26% had echocardiographic evidence of PH. Ventilation days were longer for cases than controls (mean 31 vs. 15 days, p < 0.05). Of the 17 SNPs, rs2781666 in arginase I gene was less common in cases (MAF = 0.23) than controls (MAF = 0.37, p = 0.04). The odds of PH decreased by 43% (p = 0.047) for each copy of the SNP minor allele in arginase I gene in patients with BPD. CONCLUSION: Arginase I SNP (rs2781666) may be associated with protection against pulmonary hypertension in preterm neonates with BPD.